2018
DOI: 10.22146/gamaijb.24020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training and Development and Supervisor Support on Employees Retention in Academic Institutions: The Moderating Role of Work Environment

Abstract: This study investigated the impact of training and development and supervisors support on employees retention. Furthermore, the current study also investigates the moderating effect of the work environment on the relationship between training and development, supervisors support, and employees' retention. A survey was undertaken to collect data from 250 faculty members working in public sector universities in Pakistan. PLS path modeling was employed to analyze the data. The results revealed that training and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 40 publications
9
88
1
9
Order By: Relevance
“…Ahmad, Bibi. P., Khalid, M.M., & Aziz, 2017;Bibi et al, 2017). Training is a costly activity yet organizations pay special attention to T&D programs to enhance the employee commitment level (Elangovan & Karakowsky, 1999;Lamba & Choudhary, 2013).…”
Section: Training and Development And Organizational Commitmentmentioning
confidence: 99%
“…Ahmad, Bibi. P., Khalid, M.M., & Aziz, 2017;Bibi et al, 2017). Training is a costly activity yet organizations pay special attention to T&D programs to enhance the employee commitment level (Elangovan & Karakowsky, 1999;Lamba & Choudhary, 2013).…”
Section: Training and Development And Organizational Commitmentmentioning
confidence: 99%
“…Previous researches reported that supervisors not only influence employees' state of work-life balance but also have a significant impact on the success of formal and informal work-life procedures (Talukder et al, 2018). Supervisors' support should include the beneficial evaluation of employee's performance, facilitate favorable attitudes towards the work environment in general, profession mentoring, the development of employee's career networks and job direction (Bibi et al, 2018). While the relationship between employees and supervisors is characterized by obligation, faith, long-term orientation, and emotional-social aspects, employees consider support for supervisors as building social interchange (Eisenberger et al, 2002 andDysvik andKuvaas 2013).…”
Section: Organization's Leadership and Supervision (Ols)mentioning
confidence: 99%
“…The study of Bibi et al (2018) found that employees' retention is significantly linked with the supervisory support and training and development. In addition to that, the study of Bibi et al (2018) considered the moderating role of work environment to establish the relationship between aforementioned variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of Bibi et al (2018) found that employees' retention is significantly linked with the supervisory support and training and development. In addition to that, the study of Bibi et al (2018) considered the moderating role of work environment to establish the relationship between aforementioned variables. On the other hand, employees' self-construal is a significant moderator in strengthening the relationship between employees' organizational commitment and perception of employees towards existing training (Yang, Sanders and Bumatay, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%